Does the green credit policy affect the carbon emissions of heavily polluting enterprises? - Chuanwang Sun; Yingfang Zeng (Energy Policy, 2023)

Integration of small RNAs, degradome, and transcriptome sequencing provides insights into the differences between Shizhu ginseng and Yuan ginseng - Mengyuan Peng; Yanlin Chen; Wenjuan Wang; Zhihua He; Wangqiang Dai; Zhiyun Lin; Zemin Yang; Mengjuan Gong; Yongqin Yin; Bin Han; Yu Zeng; Yingfang Wang (Journal of Plant Biochemistry and Biotechnology, 2021)
Panax ginseng is one of the most popular herbs which have been used as an important traditional Chinese medicine since ancient times. Yuan ginseng and Shizhu ginseng,which belong to P. ginseng , are widely used as substitutes for wild ginseng in clinical practice. Clinical practice has proved that the clinical efficacy of Shizhu ginseng is better than Yuan ginseng. However, current research cannot completely explain this phenomenon. Considering that small RNA may be one of the pharmacodynamic substances of P. ginseng , it is challenging to investigate differential miRNAs between Shizhu ginseng and Yuan ginseng. In this study, the transcriptome, small RNAome and degradome of P. ginseng were studied by high-throughput sequencing. A total of 63,875 unigenes and 43,950,137 small RNA clean reads were obtained from the roots of P. ginseng . Among 3206 differentially expressed genes, 1190 genes were up-regulated in Yuan ginseng when compared with Shizhu ginseng. 24 known differential miRNAs and 7 novel differential miRNAs were obtained. The 304 targets of 24 differentially expressed miRNA (17 known and 7 novel) families are mainly related to energy metabolism, biotic stress and disease immunity in ginseng itself. Through the association analysis of mRNA and miRNA, our work gives a better understanding of the difference between Yuan ginseng and Shizhu ginseng. Considering the cross-kingdom regulation of plant miRNAs, our results may provide a foundation for understanding the miRNA-dependent clinical efficacy in P. ginseng .